Affordable grain protection - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
In July 2001, Charles Mbambo wrote from Zimbabwe that 'maize harvesting is now over, and everyone is looking forward to storing the grain. It has to be protected against weevils but the price of pesticides is unaffordable for poor farmers. Dear...